Ultrasound Improves Gallbladder Contraction Function: A Non-Invasive Experimental Validation Using Small Animals - Run Guo; Tian Chen; Fan Ding; Li-Ping Liu; Fang Chen; Gang Zhao; Bo Zhang (Bioengineering)
Background: Gallbladder hypomotility is a key pathogenic factor in cholelithiasis. Non-invasive interventions to enhance gallbladder contractility remain limited. Ultrasound therapy has shown promise in various muscular disorders, but its effects on gallbladder function are unexplored. Methods: This study employed low-intensity pulsed ultrasound (LIPUS) at a 3 MHz frequency and 0.8 W/cm2 intensity with a 20% duty cycle to irradiate the gallbladder region of fasting guinea pigs. Gallbladder contractile function was evaluated through multiple complementary approaches: in vivo assessment via two-dimensional/three-dimensional ultrasound imaging to monitor volumetric changes; quantitative functional evaluation using nuclear medicine scintigraphy (99mTc-HIDA); and ex vivo experiments including isolated gallbladder muscle strip tension measurements, histopathological analysis, α-smooth muscle actin (α-SMA) immunohistochemistry, and intracellular calcium fluorescence imaging. Results: Ultrasound significantly enhanced gallbladder emptying, evidenced by the volume reduction and increased ejection fraction. Scintigraphy confirmed accelerated bile transport in treated animals. Ex vivo analyses demonstrated augmented contractile force, amplitude, and frequency in ultrasound-treated smooth muscle. Histological examination revealed smooth muscle hypertrophy, α-SMA upregulation, and elevated intracellular calcium levels. Extended ultrasound exposure produced sustained functional improvements without tissue damage. Conclusions: Ultrasound effectively enhances gallbladder contractile function through mechanisms involving smooth muscle structural modification and calcium signaling modulation. These findings establish the experimental foundation for ultrasound as a promising non-invasive therapeutic approach to improve gallbladder motility and potentially prevent gallstone formation.